Body composition and performance in cross-country skiing - Larsson, P.; Henriksson-Larsen, K. (International Journal of Sports Medicine, 2008)
The purpose of this study was to investigate the relationships between body composition and performance in cross-country skiing. Ten male college-aged elite cross-country skiers (17.9 yrs; S 1.0 yrs) participated in a 5.6-km cross-country skiing time trial and in dual energy X-ray absorptiometry (DXA, Lunar DPX-L, Madison, WI, USA) body composition measurements. A differential global positioning system (dGPS, GPS 12 CX, Garmin Int. Inc., Olathe, KS, USA; RXMAR 2, Aztec SA, Strasbourg, France) was used to compute speed in different sections of the course. Spearman correlation analyses were applied. Total body weight and absolute lean body mass were significantly related to final time (r = - 0.721; p < 0.05 and - 0.830; p < 0.01, respectively). Absolute lean arm mass (kg) was negatively correlated to final time (r = - 0.648; p < 0.05) and the relative lean arm mass was significantly related to speed mainly in uphill sections (r = 0.636 to 0.867; p < 0.05 to p < 0.01). We suggest that large amounts of lean body mass, especially in the arms, seem to be of great importance for cross-country skiing performance.